The Reformation and the university church in Leipzig: Uses of the past to support the rebuilding of a disputed religious heritage - Groop, Kim (Approaching religion, 2023)
The purpose of this article is to investigate how memory activists from 2008 onwards used the past in their advocacy work for the restoration of the university church in Leipzig. The Paulinerkirche was built as a Dominican monastery church in the first half of the thirteenth century. In 1545, shortly after the Reformation had reached Leipzig, it was reconsecrated by Martin Luther and became the first Protestant university church in Germany. Following the demands of the GDR state, it was destroyed in 1968. In writings, demonstrations and speeches, advocates of church rebuilding made use of the Reformation, but also of other tropes in the local history to draw attention to their cause. The goal was not to create a new Reformation site; rather, the aim was to compel the university leadership to abandon its goal to build a multi-purpose value-neutral assembly hall and instead honour its cultural and religious heritage, undo some of the damage done in 1968 and allow the return of the university church.